A bad, bad place - Crawford, Frances, 1962- (Soho Press, 2026)
"If it hadn't been for her wee stupid dog Sid Vicious, 12-year-old Janey Devine might never have stumbled upon the corpse of Samantha Watson. And then maybe she'd still be able to sleep at night. And maybe her nana wouldn't be so worried sick all the time. And maybe Billy "The Ghost" Watson, a notorious gangster, wouldn't be on her tail--for it's Billy's daughter who was left for dead on those train tracks, and now Billy wants answers. Fear and gossip spread through the tight-knit community of Possilpark, Glasgow, and while Janey swears she can't remember the details of that morning, the cops think she's hiding something--and indeed, there's something she knows that she's not quite ready to tell anyone else, not even her nana, who won't rest until this whole thing is behind them."-- Provided by publisher.